2020
DOI: 10.1111/cpr.12931
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell analysis identified lung progenitor cells in COVID‐19 patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…The gene expression dataset of bronchoalveolar lavage fluid of COVID‐19 patients shows that there are some similarities in the cytokine and apoptosis genes in the ARDS sequencing results induced by Staphylococcal enterotoxin B [ 39 ]. Single cell RNA sequencing of bronchoalveolar lavage fluid from COVID‐19 patients revealed significant amplification of transmembrane 4 L six family member 1 (TM4SF1)+ and keratin 5 (KRT5)+ lung progenitor cells in severe COVID‐19 patients, suggesting a synergistic role of lung progenitor cells in the prevention and supplementation of alveolar loss in COVID‐19 patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene expression dataset of bronchoalveolar lavage fluid of COVID‐19 patients shows that there are some similarities in the cytokine and apoptosis genes in the ARDS sequencing results induced by Staphylococcal enterotoxin B [ 39 ]. Single cell RNA sequencing of bronchoalveolar lavage fluid from COVID‐19 patients revealed significant amplification of transmembrane 4 L six family member 1 (TM4SF1)+ and keratin 5 (KRT5)+ lung progenitor cells in severe COVID‐19 patients, suggesting a synergistic role of lung progenitor cells in the prevention and supplementation of alveolar loss in COVID‐19 patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the selected hub genes, we found that HLA‐G and OCLN genes were reported to be related to COVID‐19 in previous studies. Lung progenitor cells of KLT5 + can differentiate into HOP homeobox (HOPX)+ OCLN+ alveolar barrier cells to supplement alveolar loss after SARS‐CoV‐2 infection, restore epithelial barrier and effectively prevent infiltration of inflammatory cells [ 40 ]. Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…ScRNAseq consists in obtaining gene expression profiling at a single-cell resolution, putting in evidence the different cellular states and molecular dynamics of even the rarer subpopulations. This novel technology has been used successfully in several organs—for example, to study Prominin 1+ liver progenitors [ 114 ], Dach1–downregulated lymphoid progenitors [ 115 ] and KTR5+ lung progenitors in COVID-19 patients [ 116 ]. Within the past few years, an increasing number of research groups have applied this strategy to define the cell populations of the kidneys in mice and humans [ 117 , 118 , 119 , 120 ].…”
Section: Outlook On the Future Of Renal Progenitorsmentioning
confidence: 99%
“…ScRNAseq consists in obtaining gene expression profiling at a single-cell resolution, putting in evidence the different cellular states and molecular dynamics of even the rarer subpopulations. This novel technology has been used successfully in several organs-for example, to study Prominin 1+ liver progenitors [114], Dach1-downregulated lymphoid progenitors [115] and KTR5+ lung progenitors in COVID-19 patients [116]. Within the past few years, an increasing number of research groups have applied this strategy to define the cell populations of the kidneys in mice and humans [117][118][119][120].…”
Section: Regulators Of Tubular Progenitors In Pathology: a Cacophonus Choirmentioning
confidence: 99%